Neem-derived silver-decorated RGO/ZnO heterostructure nanocomposite: A bifunctional material for sunlight-driven photocatalysis and solar energy conversion - Muthusamy, Kandasamy; Rameshkumar, Perumal; Islam, Mohammad Aminul; Gnanasekaran, Lalitha; Paranthaman, Vijayakumar; Shanmugapriya, Dharani; Arith, Faiz (Elsevier B.V., 2026)
In this study, neem extract was used as both a reducing and capping agent in environmental production in silver/ graphene/zinc oxide ternary nanocomposite (Ag/RGO/ZnO NC). Highly densed pebble-stone like Ag/ZnO crystalline nanostructures embedded with RGO sheets were identified through high-resolution transmission electron microscopy (HRTEM). The photocatalytic activity of the green-synthesized Ag/RGO/ZnO NC was evaluated by examining its efficiency in degrading Rhodamine B (RhB) under exposure to sunlight irradiation. The nanocomposite disclosed a significant photocatalytic degradation efficiency of RhB dye with 99.8% due to the generation of hydroxyl radical (●OH), evidenced by terephthalic acid fluorescence study. Similarly, the dyesensitized solar cell (DSSC) efficiency of the green synthesized samples has also been explored under 1 sun. It was found that Ag/RGO/ZnO DSSC delivered a high power conversion efficiency (PCE) 4.04%, that ~45% higher than pure ZnO DSSC can be credited to the accordance of Ag and RGO, acting as electron rich, and good interfacial electron mobility. Thus, this study further credits the greener fabrication of photocatalysts and dyesensitized solar cell efficiency.